MODELLING GAIT SYNDROME IN HUNTINGTON’S DISEASE: THE GENETIC ALGORITHM APPROACH (Nigerian Journal of Technology, 2017)
Huntington’s disease (HD) which usually affects the patients at middle age results from malfunctioning of the basal ganglia. It is characterized by cognitive impairment, involuntary movements, neuropsychiatric and psychological disturbances. Early motor signs of Huntington’s disease typically include the gradual onset of clumsiness, balance difficulties, and brief, random, fidgeting movements. A popular approach to solving symptoms arising from HD has been through the administration of drugs. But drugs debase human activities, thus the application of electroconvulsive therapy. This work proposes a genetic algorithmic (GA) simulation of chorea in HD patient as a pedestal for the design of a therapeutic device aimed at managing the phenomenon. Earlier efforts have led us to the formulation of such models in recent past. We also compared the GA model with our foremost effort: the electromechanical model, and we observe that the GA model adequately capture the physiological presentation of gait phenomenon in Huntington’s disease. http://dx.doi.org/10.4314/njt.v36i3.37